Amniotic Fluid Embolism. Is a New Pregnancy Possible? Case Report - Ana Filipa Cabrita Caeiro; Irina Dulce Tapadinhas Matos Ramilo; Ana Paula Santos; Elizabeth Ferreira; Isabel Santos Batalha (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Amniotic fluid embolism (AFE) is a rare but potentially catastrophic clinical condition, characterized by a combination of signs and symptoms that reflect respiratory distress, cardiovascular collapse and disseminated intravascular coagulation (DIC). Its pathogenesis is still unclear. More recently, the traditional view of obstruction of pulmonary capillary vessels by amniotic fluid emboli as the main explanation for the etiology has been ruled out, and immunologic factors and the activation of the inflammatory cascade took on an important role. Amniotic fluid embolism has an unpredictable character, its diagnosis is exclusively clinical, and the treatment consists mainly of cardiovascular support and administration of blood products to correct the DIC. No diagnostic test is recommended until now, though multiple blood markers are currently being studied. The authors present a case report of a woman who had survived AFE in her previous pregnancy and had a subsequent pregnancy without recurrence, providing one more clinical testimony of the low risks for the pregnancy after AFE.